Refractive Status Characteristic in School-Aged Children: Cicendo National Eye Hospital Vision Screening Program - Susilo, Nathasya Maharani; Ratnaningsih, Nina; Rini, Mayang (Majalah Oftalmologi Indonesia, 2026)
Introduction: Refractive error is a major cause of visual impairment in school-age children and can be detected early through vision screening programs. This study aimed to describe the characteristics of refractive errors among school-age children participating in a vision screening program at the Community Ophthalmology Unit, National Eye Center Cicendo Eye Hospital. Methods: A retrospective cross-sectional study was conducted using vision screening data from January–December 2023. Visual acuity and non-cycloplegic refraction were examined by trained personnel. Data were analyzed descriptively using Microsoft® Excel. Results: A total of 1,411 children were included, with 488 (17%) experiencing visual impairment. Myopia was the most common refractive error, mainly mild myopia and moderate astigmatism. Severe visual impairment (1.02%) was still found despite best corrected visual acuity. Refractive errors were most frequent among 11-year-old students (26%). Conclusion: The prevalence of refractive errors in school-age children remains high, with myopia as the most common type. Routine vision screening programs are still necessary for early detection and management.